Trends of Cutaneous Squamous Cell Carcinoma in the Hospital of Gaia (2004-2013) - Costa Campos, Manuel António (2018)
Introduction: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer and its incidence has been rising. The objective of our study was to perform a descriptive and analytical analysis of the cutaneous squamous cell carcinoma excised in the Hospital Center Vila Nova de Gaia e Espinho (CHVNGE) over a period of 10 years and establish trends (incidence, survival and mortality).Material and Methods: Information was retrospectively gathered in the CHVNGE, from January 2004 to December 2013, using the regional cancer registry and the histopathological registry of the hospital. The aim of this study was to describe the characteristics and trends of cutaneous squamous cell carcinoma (incidence, association with actinic keratosis or basal cell carcinoma, survival and mortality rates).Results: 485 cutaneous squamous cell carcinoma were surgically removed in a total of 380 patients (56.1% men and 43.9% women). 361 patients presented invasive cutaneous squamous cell carcinoma and 124 in situ cutaneous squamous cell carcinoma. The Dermatology Department removed 70.4% of the cutaneous squamous cell carcinoma, followed by the Plastics (16.4%) and General Surgery Departments (4.7%). Cutaneous squamous cell carcinoma was more prevalent in the age-group ≥75-years in both sexes (p < 0.001).The mean age of invasive cutaneous squamous cell carcinoma was 76.7 years (±11.5 years), women being older than men (79.0 vs 74.0 years, p < 0.001). The face was the most common topographic location (42.1%), in both genders (p < 0.001). We observed a rising incidence in both genders, particularly in the last study period (16.2/100 000 person-year). The 5-year survival rate was 98.7%. The mean age of in situ cutaneous squamous cell carcinoma was lower than invasive disease (75.5 years ± 11.3). A previous basal cell carcinoma occurred in 20.6% and actinic keratosis were diagnosed more frequently in women (p = 0.040). The face was the most common location (30.8%). Incidence rates have risen, particularly in women and age-group ≥ 75-years.Conclusion: Our study reports a rapid increase of the incidence in an ageing Portuguese population and highlights the importance of improving the existing cancer registries in Portugal.